The Effect of Adding Kaliandra Leaf Flour on Broiler Chicken Performance - Wardana, Afriyansah Bimaseta; Yakin, Engkus Ainul (Jurnal Biologi Tropis, 2025)
Since broiler production is one of the sources of animal protein that the community consumes in large quantities, efforts are being made to improve its quality and efficiency through the addition of alternative feed ingredients. One potential feed item that can be used is kalandra flour, which is known to have bioactive compounds that can impact the performance and body composition of broiler chickens. The purpose of this study was to determine the effect of adding calliandra leaf flour on the performance of broiler chickens. This study used a completely randomized design (CRD) with four treatments and four replications. There were four broiler chicks in each replication, for a total of 64 chicks. The study treatments were: 100% control feed was used at P0, 100% control feed plus 1% calliandra leaf meal was used at P1, 100% control feed plus 3% calliandra leaf meal was used at P2, and 100% control feed plus 5% calliandra leaf meal was used at P3. Feed conversion, average daily weight gain, and feed consumption were the observed variables. There was no visible variation in the study findings for feed consumption, average daily weight gain, and feed conversion (P>0.05). According to the study findings, broiler performance was not significantly affected by the addition of calliandra meal up to 5%.